2016
DOI: 10.1016/j.cell.2016.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Collective Space-Sensing Coordinates Pattern Scaling in Engineered Bacteria

Abstract: Summary Scale invariance refers to the maintenance of a constant ratio of developing organ size to body size. Though common, its underlying mechanisms remain poorly understood. Here we examined scaling in engineered E. coli that can form self-organized core-ring patterns in colonies. We found that the ring width exhibits perfect scale invariance to the colony size. Our analysis revealed a collective space-sensing mechanism, which entails sequential actions of an integral feedback loop and an incoherent feedfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
117
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(120 citation statements)
references
References 58 publications
2
117
0
1
Order By: Relevance
“…It is also an important clinical biomarker for altered metabolism and many physiological conditions, including inflammation (Haas et al, 2015), cardiovascular diseases (Xie et al, 2016), and cancer (San et al, 2013). Finally, in combination with advances in 3D printing of cells (Cao et al, 2016), we envision that the biosensor could also be used to gain spatial information from adherent cell cultures, which would facilitate the detection of differences in metabolism within individual cells, potentially enabling the diagnosis of diseases such as cancer, artherosclerosis, and diabetes based on metabolic signatures within cells (Galluzzi et al, 2013; Wishart, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…It is also an important clinical biomarker for altered metabolism and many physiological conditions, including inflammation (Haas et al, 2015), cardiovascular diseases (Xie et al, 2016), and cancer (San et al, 2013). Finally, in combination with advances in 3D printing of cells (Cao et al, 2016), we envision that the biosensor could also be used to gain spatial information from adherent cell cultures, which would facilitate the detection of differences in metabolism within individual cells, potentially enabling the diagnosis of diseases such as cancer, artherosclerosis, and diabetes based on metabolic signatures within cells (Galluzzi et al, 2013; Wishart, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…The ability to program spatial patterns of cells could potentially impact applications such as regenerative medicine that need coordinated self-organization of cells, for example in engineered stem cell organoids [105]. A number of works have demonstrated that, in principle, programmed cell coordination is possible, such as in dark-light edge detectors [106,107], spatial patterning [108][109][110], density-based gene activation [111] and microbial consortia [112], where multiple microbial populations interact to improve a product's yield. In a multicellular coordination problem, although control action still takes place in individual cells through activation or repression of suitable genes, cells have access to the ensemble state of the entire population as obtained through diffusible signalling molecules.…”
Section: Implicit High-gain Negative Feedback Through Timescale Separmentioning
confidence: 99%
“…Furthermore, steady-state population size can be tuned through the AHL degradation rate constant, which plays a major role in the 'cell -cell communication strength'. Multicellular feedback control has recently found its application to generate scale-invariant patterns in a bacterial population [109], where a core-ring fluorescence pattern is formed whose size preserves a constant ratio with the size of the population.…”
Section: Implicit High-gain Negative Feedback Through Timescale Separmentioning
confidence: 99%
“…Additionally, the LuxR-AHL complex drove the expression of lambda repressor and further regulated CheZ expression, so as to reduce the mobility of the E. coli. Integrating many of these concepts -feedback and feedforward motifs, intercellular communication, and nutrient consumptionCao et al showed that scale-invariant patterns could be produced [101]. This is of crucial importance for understanding development in higher organisms and a clear frontier in GRN construction.…”
Section: Spatial Aspects Of Grnsmentioning
confidence: 99%